Braquistócrona - Tagliolatto, Ana Luísa Sader [UNESP] (2015)
In this work it was presented the famous brachistochrone problem and the di erent solutions through the theory of variational calculus and through the concepts of geometry and physics, involving situations with similar conditions to those of brachistochrone. Adequate didactic proposal to high school students which is also suitable for middle school students was presented